The lpf fimbrial operon mediates adhesion of Salmonella typhimurium to murine Peyer's patches. - Bäumler, A J (1996)
We investigated the role of the Salmonella typhimurium fimbrial operon formed by the genes lpfABCDE in infection of mice. A mutant in lpfC, the gene encoding the fimbrial outer membrane usher, had an approximately 5-fold increased 50% lethal dose when administered orally to mice. When mice were infected with a mixture of the lpfC mutant and isogenic wild-type S. typhimurium, the lpfC mutant was recovered in lower numbers from Peyer's patches, mesenteric lymph nodes, liver, and spleen. In an organ culture model using murine intestinal loops, lpfC mutants were shown to be associated in lower numbers than wild-type bacteria with Peyer's patches but not with villous intestine. The defect of the lpfC mutant in adhesion to Peyer's patches could be complemented by introducing lpfABCDE on a cosmid. Similarly, heterologous expression of the Salmonella lpf operon in Escherichia coli resulted in an increased adhesion to histological thin sections of Peyer's patch lymph follicles. Electron microscopic analysis of histological sections taken from Peyer's patches after intragastric infection of mice showed that, in contrast to the S. typhimurium wild type, the isogenic lpfC mutant did not destroy M cells of the follicle-associated epithelium. These data show that the Salmonella lpf operon is involved in adhesion to murine Peyer's patches.